Turnover and transferable skills in a professional service firm. Issue 1 (5th February 2019) - Olsen, Karen M; Sverdrup, Therese E; Kalleberg, Arne L
Abstract: Retaining the most valuable employees is a core priority of professional service firms (PSFs). Our study addresses turnover (quit) among employees in a PSF that hires lawyers, auditors, and management consultants. We examine the extent to which the decision to quit varies by professions, skills, and job satisfaction in a PSF in Norway. The analyses are based on a survey of employees conducted in 2013 ( N = 455) combined with information on those who quit after 28 months. We find that the sub-group of non-certified auditors quit more often than all other professional groups. In addition, we find that client-contact and transferability of skills are positively related to quits, when controlling for job satisfaction, suggesting that these skills provide employees with alternative job opportunities and greater bargaining power. These measures of skills are also positively related to job satisfaction. Our study contributes to the literature on turnover and professions by emphasizing the interplay between the skills of professional workers and job satisfaction in employees' decision to quit. In addition, we add to our understanding of the concepts of general- and firm-specific skills in a multi-profession context.